Technology-Based History Learning: Developing Students’ Historical Awareness, Identity, and Critical Reflection - Mahyul, Andi; Salam, Supardi; Malik, Agung Rinaldy (ANTHOR: Education and Learning Journal, 2026)
This study examines how technology-based history learning contributes to the development of students’ historical awareness, identity, and critical reflection in senior high schools in Makassar, Indonesia. The study employed a qualitative case study design involving 54 students and two history teachers from two senior high schools. Data were collected through classroom observation, semi-structured interviews, student reflection sheets, and documentation of learning activities. The technology-based learning activities included digital documentaries, online historical sources, visual materials, virtual museum resources, digital presentations, and collaborative discussion tools. The data were analyzed using thematic analysis. The findings reveal that technology-based history learning helped students understand historical events more concretely, connect past events with present social realities, and recognize the significance of local history in shaping cultural and national identity. The use of digital media also encouraged students to compare sources, question perspectives, recognize bias, and construct reflective interpretations of historical narratives. However, the study also found that technology alone did not automatically produce deep historical understanding. Teacher scaffolding, digital literacy, source evaluation, and reflective classroom discussion were essential to transform digital materials into meaningful historical learning. This study concludes that technology-based history learning should be designed not merely to increase engagement, but to strengthen students’ historical consciousness, identity formation, and critical reasoning. The findings offer pedagogical implications for history teachers seeking to integrate digital tools with inquiry-based and reflective learning in culturally meaningful contexts.